Zakat dan Politisasi - Robyan Bafadal (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
Poverty is one of the problems in this nation since its founding until now. There are still many poor people in Indonesia who need help. The government has made many efforts to overcome poverty, one of which is by promoting zakat. Zakat is an Islamic solution for the distribution of wealth from the rich to the poor. So it is important to form members of society who like to pay zakat. It is important to provide an understanding to members of society about the importance of zakat in life. For this reason, it is necessary to promote politicization in zakat. Understanding the importance of zakat can be done by using various means in the structure of society.